Association Between Generalized Anxiety Disorder Scores and Online Activity Among US Adults During the COVID-19 Pandemic: Cross-Sectional Analysis - Singh, Parvati; Cumberland, William G; Ugarte, Dominic; Bruckner, Tim-Allen; Young, Sean D (JMIR Publications, 2020)
BackgroundEvidence from past pandemics suggests that fear, uncertainty, and loss of control during large-scale public health crises may lead to increased pandemic-related information seeking, particularly among persons predisposed to high anxiety. In such groups, a greater consumption of information pertaining to the COVID-19 pandemic may increase anxiety. ObjectiveIn this study, we examine the association between online activity and Generalized Anxiety Disorder 7 (GAD-7) scores in the United States. MethodsWe recruited participants for an online survey through advertisements on various platforms such as Google, Facebook, and Reddit. A total of 406 adult US participants with moderate to severe (≥10) GAD-7 scores met the inclusion criteria and completed the survey. Anxiety levels measured using the GAD-7 scale formed our primary outcome. Our key independent variables were average daily time spent online and average daily time spent online searching about COVID-19 within the past 14 days. We used as controls potential confounders of the relation between our key independent variables and GAD-7 scores, namely, sleep quality, the COVID-19 Fear Inventory scale, binge drinking, substance use, prescription drug abuse, and sociodemographic attributes. ResultsLinear multivariate regression analyses showed that GAD-7 scores were higher among those who spent >4 hours online (per day) searching for information about COVID-19 (coefficient 1.29, P=.002), controlling for all other covariates. The total time spent online was not statistically associated with GAD-7 scores. ConclusionsResults from this study indicate that limiting pandemic-related online information seeking may aid anxiety management in our study population.